Adsorption of chromium (VI) from aqueous solution using various low-cost adsorbents: a comparative study - Jami, Mohammed Saedi; Jameel, Ahmed Tariq; Amosa, Mutiu Kolade; Yaacob, Mohd Hafiz (IIUM Press, International Islamic University Malaysia, 2017)
When present as a pollutant in water, the hexavalent chromium compounds are carcinogenic, corrosive on tissue, and toxic to bacteria, plant, animals and people even at low concentrations. This chapter presents an investigation of adsorption efficiency of coconut husk, sugarcane pulp residue, and powdered activated carbon as adsorbents for the removal of chromium from aqueous solution. The effects of solution pH, reaction time, adsorbent loading and agitation speed on the adsorption process were studied. Langmuir and Freundlich isotherm models were fitted to the experimental data. The Freundlich isotherm fitted better when coconut husk and sugarcane pulp residue were applied as adsorbent, however, the Langmuir model could better explain the adsorption process in the case of powdered activated carbon. Pseudo-first and pseudo-second order kinetic models were used to analyze the adsorption process. The analyses revealed that the pseudo-second order model could explain the adsorption better. Furthermore, it was found that coconut husk had the highest adsorption capacity with 2.736 mg Cr (VI) per gram adsorbent, while sugarcane pulp residue and powdered activated carbon exhibited 1.8733 and 1.3618 mg/g adsorption capacities, respectively.